Design de jogos em Realidade Aumentada para Roteiros Turísticos - Francisco Gil Guerra Coelho (2023)
In the field of Tourism, paper maps are a very relevant means of promoting itineraries and activities, as well as providing a better knowledge about different regions. This dissertation is part of an R&D project for the development of digital games with Augmented Reality (AR) using paper maps. This game is meant to be played by several players on a paper map, intending to be a primary resource of publicising tourism using the diffusion of diverse information about Portuguese regions in the form of itineraries or tourist maps. To this end, this dissertation contributes with an interactive narrative, combining the various game mechanics with a georeferenced database. In this dissertation, is presented how the game was co-created, evaluated and tested throughout the iterative process, starting with the selection of the UI (User Interface) model best suited to the intended objectives, recreated in a wireframe to carry out testing and implementation of the design model; then, the design theme to be implemented was chosen and the game's logo was designed. The game's interface elements (buttons, menus...) and player icons were created. Photographs were selected and objects were created for implementation in AR as well as sound effects.